2016
DOI: 10.1186/s12935-016-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 2 (BMP2) induces growth suppression and enhances chemosensitivity of human colon cancer cells

Abstract: BackgroundMolecular profiling of colorectal cancer (CRC) based on global gene expression has revealed multiple dysregulated signalling pathways associated with drug resistance and poor prognosis. However, the role of BMP2 signaling in CRC is not fully characterised.MethodsBioinformatics data analysis were conducted on the GSE21510 dataset. Leniviral technology was utilized to stably express BMP2 in the HCT116 CRC model. Gene expression profiling was conducted using Agilent microarray platform while data normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…Inactivation of BMP signaling increases the tumorigenicity of normal colon stem cells. [ 59 ] [ 60 ] [ 61 ] VIM VIM is a Wnt-targeted gene that is expressed in normal mesenchymal cells, and that encodes the intermediate filament protein, vimentin. Previous studies have shown that vimentin mediates both cellular structure and integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation of BMP signaling increases the tumorigenicity of normal colon stem cells. [ 59 ] [ 60 ] [ 61 ] VIM VIM is a Wnt-targeted gene that is expressed in normal mesenchymal cells, and that encodes the intermediate filament protein, vimentin. Previous studies have shown that vimentin mediates both cellular structure and integrity.…”
Section: Resultsmentioning
confidence: 99%
“…BMP7 has been linked with the metastatic capacity of colon cancer, while BMP2 has been linked with tumor suppression; therefore, BMP2 does not seem to be a part of tumor proliferation strategy. 46 , 47 , 48 It is interesting to note that SMAD4 is downregulated in colon cancer, while the BMP7 ability to promote the invasive behavior of colon cancer cells is independent of SMAD4 molecules. 49 , 50 , 51 BMP7 is not the only BMP to be linked with tumor proliferation in colon cancer.…”
Section: Hepcidin Regulation In Cancermentioning
confidence: 99%
“…In addition, colonic epithelia isolated from intestine specific and global CASR knockout mice demonstrated increased proliferation and increased WNT/CTNNB1 (β‐catenin) signaling . Also, stimulation of the CASR increased the expression of BMP2 (bone morphogenetic protein‐2), which induces growth suppression and enhances chemosensitivity of human colorectal cancer cells . Furthermore, CASR activation stimulated paracrine secretion of WNT5A from myofibroblasts and expression of ROR2 in epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…15,39 Also, stimulation of the CASR increased the expression of BMP2 (bone morphogenetic protein-2), 40 which induces growth suppression and enhances chemosensitivity of human colorectal cancer cells. 41 Furthermore, CASR activation stimulated paracrine secretion of WNT5A from myofibroblasts and expression of ROR2 in epithelial cells. 42 CASR-mediated WNT5A/ROR2 interaction increased epithelial differentiation and reduced expression of the receptor for tumor necrosis factor 1.…”
Section: Cancer Epidemiologymentioning
confidence: 99%